Presidential Decree-Laws Nos. 49-50/2014 On Amending Certain Provisions of the Penal Code, Criminal Procedure Law, and Law No. 396/1956 Concerning Organizing Prisons - egypt (2025)
Presidential Decree-Law No. 49 of the year 2014 on amending certain provisions of the penal code, criminal procedure law, and law no. 396 of the year 1956 concerning organizing prisons -- Presidential Decree-Law No. 50 of the year 2014 on amending certain provisions of the penal code promulgated by law no. 58 of the year 1937 قرار رئيس جمهورية مصر العربية بالقانون رقم 49 لسنة 2014 بتعديل بعض أحكام قوانين العقوبات والإجراءات الجنائية والقانون رقم 369 لسنة 1956 فى شأن تنظيم السجون -- قرار رئيس جمهورية مصر العربية بالقانون رقم 50 لسنة 2014 بتعديل بعض أحكام قانون العقوبات الصادر بالقانون رقم 58 لسنة 1937